Allergic conjunctivitis and dry eye. Issue 11 (November 1996) - Fujishima, H; Toda, I; Shimazaki, J; Tsubota, K
Abstract : AIMS: Differential diagnosis of allergic conjunctivitis or dry eye is sometimes very difficult to diagnose by symptoms and clinical examination alone, especially in older patients. It was hypothesised that clinically allergic patients who were serum antigen specific IgE negative were candidates for dry eye. METHODS: Sixty patients were studied prospectively who were clinically diagnosed with allergic conjunctivitis by their itchy sensation and papilla formation of conjunctiva. They consisted of 30 serum antigen specific IgE positive and 30 IgE negative patients, with no significant differences in age. Dry eye examination and serum total IgE were performed on these two groups. RESULTS: No significant differences were seen between the two groups with regard to age (p = 0.76) and sex ratio. The antibody negative group had lower Schirmer's test scores (p = 0.002), lower tear clearance (p = 0.0001), lower tear function index (p = 0.0001), and lower serum total IgE (p = 0.04) than the antibody positive group. CONCLUSION: This study suggests that the evaluation of serum antigen specific IgE and tear dynamics are important for the differential diagnosis of patients with allergic conjunctivitis and dry eye. Clinically diagnosed allergic conjunctivitis with negative serum antigen specific and total IgE can be one form of dry eye.